The adoration of Jenna Fox - Pearson, Mary E. (The Jenna Fox chronicles, 2008)
In the not-too-distant future, when biotechnological advances have made synthetic bodies and brains possible but illegal, a seventeen-year-old girl, recovering from a serious accident and suffering from memory lapses, learns a startling secret about her existence.